Perubahan Mata Pencaharian Petani sebagai Dampak Alih Fungsi Lahan Pertanian : (Kajian Penelitian di Kecamatan Bacukiki Kota Parepare) - Pratiwi MK; Andi Nuddin; Iradhatullah Rahim (Jurnal Galung Tropika, 2024)
The population of Parepare City, South Sulawesi, has increased yearly. It causes a high need for housing. Unsurprisingly, land that is strategic for agriculture is then used as housing. The economic level of society also influences the conversion of agricultural land. People who cannot meet their daily needs through sales of agricultural activities, which are generally low, try to find other forms of business that can improve their welfare. This research aims to determine the pattern of changes in farmers' livelihoods due to the conversion of agricultural land. This research uses a quantitative descriptive approach. The samples taken were 52 farmers who had sold their agricultural land. Then, the next stage of analysis uses the Wilcoxon test analysis. The research results show that 26.92% of farmers whose land has been converted still work in the agricultural sector, 65.39% in the non-agricultural sector, and 7.69% do not. The conversion of agricultural land to non-agricultural land was expected to improve farmers' economic conditions. However, these conditions are not what is happening in society. The research results show no real influence between the farmers' income before and after the land is converted.